2016
DOI: 10.1002/gcc.22362
|View full text |Cite
|
Sign up to set email alerts
|

Genomic aberrations frequently alter chromatin regulatory genes in chordoma

Abstract: Chordoma is a rare primary bone neoplasm that is resistant to standard chemotherapies. Despite aggressive surgical management, local recurrence and metastasis is not uncommon. To identify the specific genetic aberrations that play key roles in chordoma pathogenesis, we utilized a genome-wide high-resolution SNP-array and next generation sequencing (NGS)-based molecular profiling platform to study 24 patient samples with typical histopathologic features of chordoma. Matching normal tissues were available for 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 49 publications
8
63
1
Order By: Relevance
“…The most common chromosomal changes in chordoma are the gain of 1q, 5, 6 and 7 and the loss of 1p, 3, 4, 9, 10, 13, 14 and 18 8 40–45. Furthermore, the chromosomal copy number loss was significantly more than the gain,38 40 and thus most studies suggest that the development of chordoma may lie in molecular mechanisms mediating copy number loss 38. Interestingly, the aberration analysed using the OncoScan array detection of BNCT/EPs showed that copy number gain in large fragments was very common, which is different from chordoma.…”
Section: Discussionmentioning
confidence: 99%
“…The most common chromosomal changes in chordoma are the gain of 1q, 5, 6 and 7 and the loss of 1p, 3, 4, 9, 10, 13, 14 and 18 8 40–45. Furthermore, the chromosomal copy number loss was significantly more than the gain,38 40 and thus most studies suggest that the development of chordoma may lie in molecular mechanisms mediating copy number loss 38. Interestingly, the aberration analysed using the OncoScan array detection of BNCT/EPs showed that copy number gain in large fragments was very common, which is different from chordoma.…”
Section: Discussionmentioning
confidence: 99%
“…At first sight, chordoma is not a promising candidate for immunotherapy, considering the abundance of extracellular matrix and the low mutational burden, 12 a commonly accepted criterion suggesting limited tumor immunogenicity. 9 However, as extensively described in the context of melanoma, 13 the rapid onset of vitiligo after chemotherapy for patient 1 was suggestive of a cross-reactive immune reaction to both melanocytes and tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…This research has resulted in the opening of a recent phase II clinical trial using Afatinib, a third generation EGFR inhibitor. Finally, cancer driver events have also been identified in chromatin remodeling genes including SETD2 , ARID1A , and PBRM1 raising the possibility that chordoma may be susceptible to epigenetic inhibitors …”
Section: Chordomamentioning
confidence: 99%
“…Finally, cancer driver events have also been identified in chromatin remodeling genes including SETD2, ARID1A, and PBRM1 raising the possibility that chordoma may be susceptible to epigenetic inhibitors. 49,59,60 Poorly differentiated chordoma was first described by Mobley et al as tumors with cohesive epithelioid morphology, marked pleomorphism, and mitotic activity. They express TBXT and cytokeratins but unlike conventional chordoma additionally reveal loss of SMARCB1 expression on immunohistochemistry.…”
Section: Brachyury (Tbxt) Expression Detected By Immunohistochemistrymentioning
confidence: 99%